2021
DOI: 10.1155/2021/2464269
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Disorder Genes Regulate the Progression of Ischemic Stroke through the NF‐κB Signaling Pathway

Abstract: Stroke is an acute cerebrovascular disease, including ischemic and hemorrhagic stroke. Stroke is the second leading cause of death after ischemic heart disease, which accounts for 9% of the global death toll. To explore the molecular mechanisms of the effects of the dysregulated factors, in the GEO database, we obtained transcriptome data from 24 h/72 h of mice with ischemic stroke and 24 h/72 h of normal mice. We then performed differential gene analysis, coexpression analysis, enrichment analysis, and regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Nuclear factor-κB (NF-κB) refers to a variety of cellular functions, including hematopoiesis, apoptosis, immune responses and inflammation [30]. It is showed that NF-κB could regulate the secretion of various pro-inflammatory factors in nerve cells, containing TNF-α, IL-6, and IL-1β [31].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor-κB (NF-κB) refers to a variety of cellular functions, including hematopoiesis, apoptosis, immune responses and inflammation [30]. It is showed that NF-κB could regulate the secretion of various pro-inflammatory factors in nerve cells, containing TNF-α, IL-6, and IL-1β [31].…”
Section: Discussionmentioning
confidence: 99%
“…The novelty of the current study may be that it compared CAD patients with other stages of heart ischemia, such as MI and ICM, versus controls on live blood and cardiac samples to monitor common DEGs through ICM development. To the best of our knowledge, most researchers have performed global gene expression to obtain key genes in the underlying mechanisms of ICM alone [40][41][42] , resulting in limited information on the contributing DEGs in ICM development through CAD and MI, especially compared to controls comprising live blood and left ventricle biopsies.…”
Section: Interaction Scores and K-means Clustering Of The Enriched Fu...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%